Moldova Financial Sector Assessment Program : Insolvency and Creditor/Debtor Regimes--Report on the Observance of Standards and Codes - World Bank (Washington, DC, 2015)
The World Bank assessed the insolvency and creditor or debtor regimes (ICR) of Moldova pursuant to the joint international monetary fund (IMF) and World Bank initiative on the observance of standards and codes (ROSC). The Moldovan authorities have made remarkable progress over the last decade in taking on board a broad range of reform related to the commercial law regime, including the laws pertaining to creditor protection and insolvency. Loans are often over collateralized, reducing available credit and increasing the incentives for lenders to rely primarily on their collateral for repayment rather than to support restructuring efforts. The secured transactions regime requires improvement, importantly regarding the facilitation of important credit instruments over category of assets. The rules aimed at encouraging good corporate behavior at times of financial distress may be improved and obstacles on insolvency filing by creditors removed to ensure timely filing of insolvency proceedings. There are also certain risks to creditor rights, including through abuse of the process by other creditors, which may disincentive the use of the system. The insolvency regime is now much more modern, but it has implementation problems, and some aspects of the law may require strengthening, including the cumbersome criteria for initiating insolvency proceedings by creditors, the lack of rules that incentivize new lending to the business in insolvency, the rules regarding transaction avoidance, due process aspects and some other rules adversely affecting creditor rights, the law and practice concerning the use of encumbered assets, and the decision-making process during insolvency especially in a restructuring context. The recommendations in this report are presented with the hope that they will assist the authorities in their continuing efforts to enhance the country’s legal and regulatory framework for enterprise credit.